1994
DOI: 10.2307/2137279
|View full text |Cite
|
Sign up to set email alerts
|

Differential Influence of Parental Smoking and Friends' Smoking on Adolescent Initiation and Escalation and Smoking

Abstract: peer smoking on adolescents' own smoking is still a matter of debate. In addition, little research has examined the role of sign8cant others' behavior on different stages of smoking onset. In particular, not much information is available regarding gender and ethnic differences in social influences on smoking behavior. We use structural equation modeling to address these issues. Different theoretical perspectives from cognitive-affective theories (Ajzen 1985; Ajzen and Fishbein 1980) and social learning theorie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

22
250
1
2

Year Published

1997
1997
2013
2013

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 405 publications
(275 citation statements)
references
References 38 publications
22
250
1
2
Order By: Relevance
“…There is considerable evidence in the literature that the smoking behaviour of friends has a major influence on the current and future smoking of adolescents and young adults (Flay et al, 1994(Flay et al, , 1998Distefan et al, 1998;Engels et al, 1999;Chassin et al, 2000;Leatherdale et al, 2005). If, as our study found, MZ pairs are more similar in their friends' smoking behaviours than are DZ pairs, this could explain some or all of the greater correlation of smoking observed in MZ twins.…”
Section: Discussionsupporting
confidence: 56%
“…There is considerable evidence in the literature that the smoking behaviour of friends has a major influence on the current and future smoking of adolescents and young adults (Flay et al, 1994(Flay et al, , 1998Distefan et al, 1998;Engels et al, 1999;Chassin et al, 2000;Leatherdale et al, 2005). If, as our study found, MZ pairs are more similar in their friends' smoking behaviours than are DZ pairs, this could explain some or all of the greater correlation of smoking observed in MZ twins.…”
Section: Discussionsupporting
confidence: 56%
“…These effects of mother's lifetime smoking likely capture a variety of environmental factors, for example exposure to secondhand smoke, which increases the risk of ND (Belanger et al, 2008;Okoli, Richardson, Ratner, & Johnson, 2009), behavioral modeling (Kalesan et al, 2006;Pedersen & Lavik, 1991), parental views of smoking (Banks et al, 1981;Flay et al, 1994;Nolte et al, 1983), and perceived availability of cigarettes (Doubeni et al, 2008;Doubeni, Li, Fouayzi, & DiFranza, 2009;Woodruff et al, 2003). Additionally, mother's lifetime smoking may transmit separate genetic risks than does MSP, since specific genetic factors influence different aspects of smoking independently (Maes et al, 2004).…”
Section: Discussionmentioning
confidence: 99%
“…These protective factors likely operate during adolescence and young adulthood when initiation of use of both alcohol and tobacco is most common. Certain environmental influences during adolescence such as peers, parents, and religious beliefs, may limit both exposure to alcohol and exposure to tobacco during this time in life (Cohen et al, 1994;Flay et al, 1994;Flay et al, 1999). However, longitudinal studies also have shown that there is a bidirectional influence between smoking and alcohol initiation in adolescence that appears to be independent of common potential third factors (Jackson et al, 2002;Wetzels et al, 2003).…”
Section: Smoking Initiationmentioning
confidence: 99%